Pemanfaatan Kunjungan Posyandu Lansia Dengan Derajat Kesehatan Lansia - Heri Hermansyah; Firda Firda (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
The elderly’s Posyandu is one of the government programs in overcoming health and social welfare problems for the elderly. Based on the results of a preliminary study at the UPTD Puskesmas Kuningan, West Java, it was found that the coverage of elderly’s posyandu visits had only get 36.14%. That score is still very far from the Indonesian National Standard that 80%. The purpose of this study was to identify whether there was a significant relationship between the use of posyandu visits by the elderly and the health status of the elderly in the working area of UPTD Puskesmas Kuningan. This study used a cross-sectional research design with an analytical observational approach. 93 elderly being respondents in this study were taken using the proportional stratified random sampling method. Data collection was done by using a questionnaire. Data were processed and analyzed using SPSS version 16 for windows with chi-square statistical test. The results obtained are P-value = 0.000 (< = 0.05). That means, there is a significant relationship between the use of posyandu by the elderly and their health status. The results of this study are expected to be a source of information for health workers to play an active role in increasing the interest and motivation of the elderly to take advantage of the posyandu services for the elderly in order to improve their health status.